Studi Kualitas Perairan Danau Sentani Menggunakan Bioindikator Makrobentos - Purwanto Purwanto; Suriani Br. Surbakti; Rosye H.R. Tanjung (Jurusan Biologi FMIPA Universitas Cenderawasih, 2013)
Study on the water quality of Sentani Lake has been carried out during October–November 2012 at 3 stations of observation. Observation and retrieval of macrobenthos have been done by using combination between line transect method and square plot. While for physical and chemical characteristics of water is measured in site and at laboratory. Index of variance Shannon-Wiener, Evenness and Density as well as Pollution Index were used to analyse the physical and chemical characteristics of water. Result of this study showed that Telaga Maya area (station 3) has the highest variation of macrobenthos with H’ value= 2.12 while the lowest variation (H’= 1.66) was found around Ekspo River (station 2). Based on population density of macrobenthos, Pilsbryoconcha exilis which collected in the area of Jembatan Dua River (station 1) was found as the highest population with density 9.26 ind/m2, while the lowest population density was Melanoides tuberculata with density 0.93 ind/m2. It can be concluded that based on the value of variance index and Pollution Index, the water quality of Sentani Lake belong to low-medium polluted category.Key words: water quality, macrobenthos, sentani lake and Jayapura.